Lipid accumulation modulation by garcinia atroviridis fruit extract in 3T3-L1 adipocyte cells - Darnis, Deny Susanti; Hamidon, Hanisuhana; Bakhtiar, M. Taher; Ahmad Rusmili, Muhamad Rusdi; Abd Hamid, Shafida; Zakaria, Zainul Amiruddin (Taylor & Francis Online, 2020)
Garcinia atroviridis contains hydroxycitric acid (HCA) that affects obesity and obesityrelated diseases. This paper aims to quantify the amount of (HCA) available in the fruit extract of Garcinia atroviridis and investigate the lipid modulation properties possessed by the extract in the 3T3-L1 adipocyte cell line. High-performance liquid chromatography (HPLC) analysis was used to quantify HCA in the extract, whereas differentiated adipocytes were evaluated Oil Red O staining. The expression of PPARγ and C/EBPα was investigated using western blot, and the lipid content was confirmed using leptin ELISA assay. HPLC analysis quantified about 11.35 ± 0.55 % (w/w) of HCA in the fruit extract, with a retention time of 0.9 minutes corresponding to the standard. In the adipogenesis assay, an increased co-treatment concentration was observed and inhibited the formation of intracellular lipids. According to the western blot analysis, the treatment was found to significantly affect the expression of C/EBPα proteins solely. Meanwhile, the leptin assay finding was in agreement with the adipogenesis analysis as a decrement of leptin released was noted at increased treatment concentrations. Finally, the fruit extract enhanced the adipocyte breakdown (adipolysis) process as revealed by the glycerol concentration measured in the adipolysis assay. The findings indicated that the fruit extract of G. atroviridis played a role in the alteration of lipid accumulation processes by the intervention of proteins associated with adipogenesis and enhanced adipolysis.